Milling and machining center basics - Cook, Jerome T.; Mason, Frederick (Fundamental manufacturing processes)
Milling operations are demonstrated on both simple knee mills, all the way to advanced CNC machining centers. You will learn about the milling process, manual milling machines, machining centers and toolchangers, cutters, types of milling operations, tables and workholding devices, workchanging, and operational performance.